2014
DOI: 10.1007/s11655-014-1816-4
|View full text |Cite
|
Sign up to set email alerts
|

Combination treatment with Gua Sha and Blood-letting causes attenuation of systemic inflammation, activated coagulation, tissue ischemia and injury during heatstroke in rats

Abstract: Gua Sha combined with Blood-letting after heatstroke may improve survival by ameliorating systemic inflflammation, hypercoagulable state, and tissue ischemia and injury in multiple organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…PT, APTT and D-dimer were markers reflecting coagulation function (36). Results showed that the values of PT in HSGSK were shorter than those in HS or HS-Pre-GSK (p = 0.019, p = 0.027; respectively; Fig 4B).…”
Section: Gsk2193874 Treatment At Heatstroke Onset Attenuated Coagulation Dysfunctionmentioning
confidence: 88%
See 2 more Smart Citations
“…PT, APTT and D-dimer were markers reflecting coagulation function (36). Results showed that the values of PT in HSGSK were shorter than those in HS or HS-Pre-GSK (p = 0.019, p = 0.027; respectively; Fig 4B).…”
Section: Gsk2193874 Treatment At Heatstroke Onset Attenuated Coagulation Dysfunctionmentioning
confidence: 88%
“…Heatstroke induces coagulation dysfunction. The histochemical result shows disseminating intravascular coagulation, which then promotes organ failure and induces death (36). Prothrombin time (PT), activated partial thromboplastin time (APTT) and D-dimer are used as markers reflecting disseminating intravascular coagulation (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 15 Research has indicated that Gua Sha therapy may enhance immune response and anti-inflammatory effects. 30 The pressure stimulation of Gua Sha on the skin leads to subcutaneous capillary rupture, with resultant blood leakage acting as a stimulus, initiating local aseptic inflammation response. 22 Our finding showed that the Gua Sha group exhibited increased plasma levels of 5-HT and IL-10, and decreased levels of IL-8 compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, acupuncture can improve blood distribution throughout the body Acupuncture can enhance blood circulation in the skin, increase heat dissipation, and regulate blood distribution in the visceral organs. Research has shown that Gua sha combined blood-letting after HS can improve survival by reducing systemic inflammation, hypercoagulable states, tissue ischemia, and multiple organ damage ( Aprile et al, 2015 ; Tu et al, 2015 ). XNJI combined with acupuncture on HS could help reduce the recovery time of consciousness and alleviate the injury of organs.…”
Section: External Therapies Against Hsmentioning
confidence: 99%